Adolescência, feminilidade e moda - Fabiana Cerqueira do Patrocínio (2016)
This dissertation presents the results of an investigation carried out on blogs and social medias of adolescents aged 12 and 16, on the topic of fashion. The research aimed to analyze the relationship between adolescence, Fashion and female. It starts from the assumption that such blogs could operate for some of the authors as a way to approach the female. For the analysis of the material, we used the psychoanalytic theory in dialogue with authors from other fields of knowledge. The theoretical research included the following subjects: adolescence, under the historical, cultural and psychoanalytic perspectives; identification under the psychoanalytical perspective; Fashion and clothing, under the sociological and philosophical perspectives; Women, on the theories of Freud and Lacan. We seek, in the light of these two authors, analyze the relationships between women, body and clothes. We concluded that the internet is fertile ground for contemporary identifications in the course of adolescence logical time, which, in the Ideal decay times, can be around the consumer goods. We believe, however, that the virtual space, with its multitude of options, from a cultural context that encourages individual choices and creativity, can be used for elaborations on the female, allowing the unique creation, from small details.